Comparative proteomic analyses reveal that the regulators of G‐protein signaling proteins regulate amino acid metabolism of the rice blast fungus Magnaporthe oryzae. Issue 21 (November 2014) - Zhang, Haifeng; Ma, Hongyu; Xie, Xin; Ji, Jun; Dong, Yanhan; Du, Yan; Tang, Wei; Zheng, Xiaobo; Wang, Ping; Zhang, Zhengguang
<x xml:space="preserve">Abstract</x> The rice blast fungus Magnaporthe oryzae encodes eight regulators of G‐protein (GTP‐binding protein) signaling (RGS) proteins MoRgs1–MoRgs8 that orchestrate the growth, asexual/sexual production, appressorium differentiation, and pathogenicity. To address the mechanisms by which MoRgs proteins function, we conducted a 2DE proteome study and identified 82 differentially expressed proteins by comparing five ∆Morgs mutants with wild‐type Guy11 strain. We found that the abundances of eight amino acid (AA) biosynthesis or degradation associated proteins were markedly altered in five ∆Morgs mutants, indicating one of the main collective roles for the MoRgs proteins is to influence AA metabolism. We showed that MoRgs proteins have distinct roles in AA metabolism and nutrient responses from growth assays. In addition, we characterized MoLys20 (Lys is lysine), a homocitrate synthase, whose abundance was significantly decreased in the ∆Morgs mutants. The ∆Molys20 mutant is auxotrophic for lys and exogenous lys could partially rescue its auxotrophic defects. Deletion of MoLYS20 resulted in defects in conidiation and infection, as well as pathogenicity on rice. Overall, our results indicate that one of the critical roles for MoRgs proteins is to regulate AA metabolism, and that MoLys20 may be directly or indirectly regulated by MoRgs and participated in lys biosynthesis, thereby affecting fungal development and pathogenicity.